High-gloss rapid prototyping PBT composite material and preparation method thereof

By using nucleating agents such as antimony trioxide and pentaerythritol stearate in PBT materials and crystallization accelerator, the crystallization temperature and crystallization rate of PBT are improved, and the problem of difficult crystallization of PBT materials during processing is solved, achieving the effect of high gloss rapid molding and product dimensional stability.

CN119775733APending Publication Date: 2025-04-08SHANGHAI SUNNY NEW TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411997996.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

It is difficult for PBT materials to crystallize during processing, resulting in problems such as material shrinkage, unstable product size and reduced surface gloss.

Method used

Antimony trioxide is used as the nucleation agent and pentaerythritol stearate, etc. as crystallization accelerator, and high-gloss rapid molding is achieved by increasing the crystallization temperature and crystallization rate of PBT.

Benefits of technology

The crystallization temperature and crystallization rate of PBT are improved, the cooling and curing time is shortened, the surface defects caused by post-shrinkage are reduced, and the surface gloss and dimensional stability of the product is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of plastic composite materials, and relates to a high-gloss rapid prototyping PBT composite material and a preparation method thereof.The high-gloss rapid prototyping PBT composite material is obtained by mixing PBT, a nucleating agent, a crystallization accelerant and an auxiliary in a high-speed rotating mixer according to the proportion and then conducting granulation through a double-screw extruder; the nucleating agent is antimony trioxide; the crystallization accelerant is more than one of pentaerythritol stearate, calcium stearate and zinc stearate. By optimizing the types of the nucleating agent and the crystallization accelerant of the PBT composite material, the crystallization temperature and glossiness of the PBT material are comprehensively improved, and a new solution is provided for modification and application of the PBT material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic composite materials and relates to a high-gloss rapid-molding PBT composite material and a preparation method thereof. Background Art

[0002] PBT (polybutylene terephthalate) is a semi-crystalline linear polyester material. It is widely used in electronics, automobiles, instruments, household appliances, and medical fields due to its excellent heat resistance, chemical resistance, electrical properties, and mechanical properties. As a semi-crystalline thermoplastic engineering material, the crystallinity of PBT is crucial to improving the heat resistance, chemical resistance, and mechanical properties of the material. However, during the processing, PBT materials are often difficult to complete crystallization, and the post-crystallization phenomenon will cause post-shrinkage of the material, which in turn causes problems such as unstable product size and reduced surface gloss.

[0003] Some studies have proposed solutions to improve the crystallization performance of PBT. For example, patent application CN102558791A mentions the use of inorganic minerals such as P250 or talcum powder as nucleating agents. These conventional nucleating agents can increase the crystallization temperature of PBT to a certain extent, but the improvement effect is limited. In addition, the patent application also uses polyether-type liquid plasticizer P-1000 or polyethylene glycol diglycidyl ether as a crystallization promoter. However, this type of liquid plasticizer is easy to precipitate during long-term use of the product, thereby affecting the stability and service life of the product.

[0004] Patent application CN103304965A proposes a polybutylene terephthalate composition and a preparation method thereof, wherein a sodium salt of montan wax acid is used as a nucleating agent for PBT. This organic nucleating agent has achieved good results in improving the crystallization uniformity of PBT, but the improvement of the crystallization temperature is still limited. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the prior art and provide a high-gloss rapid prototyping PBT composite material and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A high-gloss rapid prototyping PBT composite material, comprising, by weight, 100 parts of PBT, 0.5-5 parts of a nucleating agent, 0.2-1 parts of a crystallization accelerator, and 0.3-1 parts of an auxiliary agent;

[0008] The nucleating agent is antimony trioxide;

[0009] Antimony trioxide is often used as a flame retardant synergist in bromine antimony flame retardant systems and is added to PBT at the same time as glass fiber. The technicians in this field, due to the influence of glass fiber on the crystallization of PBT, have neglected the fact that antimony trioxide also has a great effect on increasing the crystallization temperature of PBT.

[0010] The present invention unexpectedly discovered this phenomenon, and used antimony trioxide to greatly increase the crystallization temperature of PBT; the higher the crystallization temperature, the faster the crystallization speed during the processing, and the faster the material cools and solidifies during the injection molding process, which can shorten the cooling time and reduce the molding cycle; the higher the crystallization temperature, the more conducive it is for the PBT composite material to replicate the high-gloss mold surface and reduce surface defects caused by post-shrinkage;

[0011] The crystallization accelerator is one or more of pentaerythritol stearate, calcium stearate, and zinc stearate;

[0012] The crystallization accelerator added to PBT in the prior art is generally a liquid plasticizer with a small molecular weight, which mainly plays a plasticizing role, allowing PBT macromolecules to move freely at a relatively low temperature, which is conducive to crystallization. However, this liquid plasticizer is easy to precipitate during the long-term use of the product, resulting in product appearance defects;

[0013] The crystallization promoter selected in the present invention has a relatively large molecular weight, is a powdery solid at room temperature, has high thermal stability and has good compatibility with PBT; when PBT is plasticized (i.e., heated to a plastic state), the crystallization promoter molecules can be inserted into PBT macromolecules or between PBT molecular chain segments, reducing the force and relative movement resistance between PBT molecules, making the PBT macromolecular chains freer in the melt and reducing their potential energy for free movement; due to the reduction in the potential energy for free movement, PBT macromolecules are more easily oriented (i.e., arranged into an ordered structure) and crystallized in the melt, which helps to increase the crystallization rate of PBT, so that the product has a more compact and ordered structure after cooling and solidification; due to the increase in crystallization rate and the optimization of molecular structure, the appearance defects (such as microscopic shrinkage and deformation, etc.) caused by post-shrinkage of the product are reduced; in addition, since the molecular weight of the crystallization promoter selected in the present invention is relatively large, it is not easy to precipitate and will not affect the appearance of the product;

[0014] Pentaerythritol stearate, calcium stearate and zinc stearate are often used as dispersants and lubricants added to plastics. The present invention firstly finds that they can increase the crystallization rate of PBT and use them as crystallization accelerators.

[0015] As the preferred technical solution:

[0016] In the high-gloss rapid-molding PBT composite material as described above, the purity of antimony trioxide is above 99.9%. The higher the purity, the fewer surface defects of the injection-molded product.

[0017] As described above, for a high-gloss rapid prototyping PBT composite material, the relative viscosity of PBT is 0.775-0.87. The lower the relative viscosity of PBT, the shorter the molecular chain, the smaller the molecular displacement resistance, and the more conducive to orientation and crystallization.

[0018] The high gloss rapid prototyping PBT composite material as described above, wherein the auxiliary agent is an antioxidant.

[0019] The high-gloss rapid prototyping PBT composite material as described above has a 60° gloss of 98.8-100.5 and a crystallization temperature of 204.2-207.3°C; after the high-gloss rapid prototyping PBT composite material is placed under environmental conditions of a temperature of 85°C and a relative humidity of 85% for 240 hours, the 60° gloss retention rate is 96.1-97.6%.

[0020] The present invention also provides a method for preparing a high-gloss rapid prototyping PBT composite material as described in any of the above items, wherein each component is mixed in a high-speed rotating mixer according to a proportion, and then granulated by a twin-screw extruder to obtain a high-gloss rapid prototyping PBT composite material.

[0021] As the preferred technical solution:

[0022] In the method described above, the rotation speed of the twin-screw extruder is 400-450 rpm, and the extrusion temperature is 210-230°C.

[0023] Beneficial effects:

[0024] (1) The present invention uses antimony trioxide as a nucleating agent, which greatly increases the crystallization temperature of PBT, breaking the limitation of antimony trioxide as only a flame retardant synergist in traditional cognition, and provides a new idea for the modification of PBT materials.

[0025] (2) The crystallization accelerator selected in the present invention has good compatibility with PBT and can reduce the interaction between PBT macromolecular chains and the friction resistance of relative molecular movement after PBT is plasticized, which helps the PBT macromolecular chains to orient and crystallize more freely in the melt, thereby increasing the crystallization rate of PBT and making the product have a more compact and orderly structure after cooling and solidification.

[0026] (3) The high-gloss rapid prototyping PBT composite material of the present invention can be cooled and solidified faster during injection molding, reducing surface defects caused by post-shrinkage, thereby improving the surface gloss and dimensional stability of the product.

[0027] (4) Compared with traditional liquid plasticizers, the crystallization accelerator selected in the present invention has a relatively large molecular weight and is not easy to precipitate, thereby avoiding appearance defects caused by plasticizer precipitation during long-term use of the product, thereby extending the service life of the product. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0029] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:

[0030] 60° gloss: tested according to GB / T 9754-2007 standard.

[0031] After being placed under the environmental conditions of temperature of 85°C and relative humidity of 85% for 240 hours, the 60° gloss retention rate = 60° gloss after placement / 60° gloss before placement × 100%.

[0032] Crystallization temperature: tested according to GB / T 19466.3-2004 standard; wherein the cooling rate is 10℃ / min.

[0033] Example 1

[0034] A method for preparing a high-gloss rapid prototyping PBT composite material, the specific steps are as follows:

[0035] (1) Preparation of raw materials;

[0036] PBT: manufacturer is Kanghui New Material Technology Co., Ltd., brand name is KH2080, relative viscosity is 0.775;

[0037] Antimony trioxide: The manufacturer is Hunan Yiyang Shanxing Antimony Industry Co., Ltd., with a purity of 99.9%:

[0038] Crystallization accelerator: pentaerythritol stearate;

[0039] Additive: a mixture of antioxidant 1076 and antioxidant 168 in a mass ratio of 1:2;

[0040] (2) PBT, antimony trioxide, a crystallization accelerator and an auxiliary agent are mixed in a high-speed rotating mixer, and then granulated by a twin-screw extruder to obtain a high-gloss rapid molding PBT composite material; wherein the speed of the twin-screw extruder is 400-450 rpm, and the extrusion temperature is 210-230°C.

[0041] The high-gloss rapid prototyping PBT composite material finally prepared is composed of 100 parts of PBT, 2 parts of antimony trioxide, 0.5 parts of crystallization accelerator and 0.5 parts of auxiliary agent by weight; the 60° glossiness of the high-gloss rapid prototyping PBT composite material is 99.1, and the crystallization temperature is 205.8°C; after the high-gloss rapid prototyping PBT composite material is placed under environmental conditions of temperature of 85°C and relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 97.2%.

[0042] Comparative Example 1

[0043] A method for preparing a PBT composite material, which is different from Example 1 only in that antimony trioxide is replaced by Licomont NaV 101 (purchased from Clariant).

[0044] The 60° glossiness of the PBT composite material finally prepared is 97.1 and the crystallization temperature is 197.8°C.

[0045] Comparative Example 2

[0046] A method for preparing a PBT composite material, which is different from Example 1 only in that antimony trioxide is replaced by BRUGGOLEN P250 (purchased from Brüggemann).

[0047] The 60° glossiness of the PBT composite material finally prepared is 97.2, and the crystallization temperature is 197.4°C.

[0048] Comparative Example 3

[0049] A method for preparing a PBT composite material, which is different from Example 1 only in that antimony trioxide is replaced by talcum powder T2 (purchased from Jiangsu Youtuoke Venture Capital Co., Ltd.).

[0050] The 60° glossiness of the PBT composite material finally prepared is 96.5 and the crystallization temperature is 196.9°C.

[0051] Compared with Example 1, the 60° gloss and crystallization temperature of the PBT composite materials in Comparative Examples 1 to 3 are significantly reduced. This is because the three nucleating agents, Licomont NaV 101, BRUGGOLEN P250 and talcum powder T2, are less effective than antimony trioxide in promoting the crystallization of PBT and improving the surface gloss of the material, and cannot effectively increase the crystallization temperature of PBT, so that PBT cannot be quickly crystallized during the processing, resulting in prolonged cooling and curing time and increased molding cycle, which is not conducive to replicating the high-gloss mold surface and reducing surface defects caused by post-shrinkage, resulting in lower 60° gloss and crystallization temperature of the finally obtained PBT composite material.

[0052] Comparative Example 4

[0053] A method for preparing a PBT composite material, which is different from Example 1 only in that the crystallization accelerator is replaced by P-1000 (purchased from Foshan Jieke New Materials Co., Ltd.).

[0054] The 60° glossiness of the finally prepared PBT composite material is 98.8; after the PBT composite material is placed under the environmental conditions of a temperature of 85° C. and a relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 85.3%.

[0055] Comparative Example 5

[0056] A method for preparing a PBT composite material, which is different from Example 1 only in that the crystallization accelerator is replaced by a polyethylene glycol diglycidyl ether liquid plasticizer (purchased from Shanghai Rufa Chemical Technology Co., Ltd.).

[0057] The 60° glossiness of the finally prepared PBT composite material is 98.9; after the PBT composite material is placed under the environmental conditions of a temperature of 85° C. and a relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 84.9%.

[0058] Compared with Example 1, the 60° gloss retention rate of the PBT composite materials in Comparative Examples 4 to 5 is significantly reduced after being placed under the environmental conditions of a temperature of 85°C and a relative humidity of 85% for 240 hours. This is because Comparative Examples 4 to 5 all use liquid plasticizers as crystallization promoters, which have a small molecular weight and are easily precipitated after being placed under the environmental conditions of a temperature of 85°C and a relative humidity of 85% for 240 hours, thereby affecting the 60° gloss of the PBT composite material and ultimately affecting the long-term stability of the product.

[0059] Example 2

[0060] A method for preparing a high-gloss rapid prototyping PBT composite material, which differs from Example 1 only in that the addition amounts of a crystallization accelerator and an auxiliary agent are adjusted during the preparation process.

[0061] The high-gloss rapid prototyping PBT composite material finally prepared is composed of 100 parts of PBT, 2 parts of antimony trioxide, 0.2 parts of crystallization accelerator and 0.3 parts of auxiliary agent by weight; the 60° glossiness of the high-gloss rapid prototyping PBT composite material is 99, and the crystallization temperature is 205.2°C; after the high-gloss rapid prototyping PBT composite material is placed under environmental conditions of temperature of 85°C and relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 97.5%.

[0062] Example 3

[0063] A method for preparing a high-gloss rapid prototyping PBT composite material, which is different from Example 1 only in that the addition amounts of antimony trioxide and auxiliary agents are adjusted during the preparation process.

[0064] The high-gloss rapid prototyping PBT composite material finally prepared is composed of 100 parts of PBT, 0.5 parts of antimony trioxide, 0.5 parts of crystallization accelerator and 1 part of auxiliary agent by weight; the 60° glossiness of the high-gloss rapid prototyping PBT composite material is 98.8, and the crystallization temperature is 204.2°C; after the high-gloss rapid prototyping PBT composite material is placed under environmental conditions of temperature of 85°C and relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 96.1%.

[0065] Example 4

[0066] A method for preparing a high-gloss rapid prototyping PBT composite material, which is different from Example 1 only in that the addition amounts of antimony trioxide and auxiliary agents are adjusted during the preparation process.

[0067] The high-gloss rapid prototyping PBT composite material finally prepared is composed of 100 parts of PBT, 3 parts of antimony trioxide, 0.5 parts of crystallization accelerator and 0.8 parts of auxiliary agent by weight; the 60° glossiness of the high-gloss rapid prototyping PBT composite material is 99.3, and the crystallization temperature is 206.1°C; after the high-gloss rapid prototyping PBT composite material is placed under environmental conditions of a temperature of 85°C and a relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 97.6%.

[0068] Example 5

[0069] A method for preparing a high-gloss rapid prototyping PBT composite material, which is different from Example 1 only in that the addition amounts of antimony trioxide and a crystallization accelerator are adjusted during the preparation process.

[0070] The high-gloss rapid prototyping PBT composite material finally prepared is composed of 100 parts of PBT, 3 parts of antimony trioxide, 1 part of crystallization accelerator and 0.5 parts of auxiliary agent by weight; the 60° glossiness of the high-gloss rapid prototyping PBT composite material is 99.8, and the crystallization temperature is 206.7°C; after the high-gloss rapid prototyping PBT composite material is placed under environmental conditions of temperature of 85°C and relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 97.1%.

[0071] Example 6

[0072] A method for preparing a high-gloss rapid prototyping PBT composite material, which is different from Example 1 only in that the addition amounts of antimony trioxide and a crystallization accelerator are adjusted during the preparation process.

[0073] The high-gloss rapid prototyping PBT composite material finally prepared is composed of 100 parts of PBT, 5 parts of antimony trioxide, 1 part of crystallization accelerator and 0.5 part of auxiliary agent by weight; the 60° glossiness of the high-gloss rapid prototyping PBT composite material is 100.5, and the crystallization temperature is 207.3°C; after the high-gloss rapid prototyping PBT composite material is placed under environmental conditions of a temperature of 85°C and a relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 97.4%.

[0074] Example 7

[0075] A method for preparing a high-gloss rapid prototyping PBT composite material, the specific steps are as follows:

[0076] (1) Preparation of raw materials;

[0077] PBT: manufacturer is Kanghui New Material Technology Co., Ltd., brand name is KH2090, relative viscosity is 0.87;

[0078] Antimony trioxide: The manufacturer is Hunan Yiyang Shanxing Antimony Industry Co., Ltd., with a purity of 99.9%:

[0079] Crystallization accelerator: pentaerythritol stearate;

[0080] Additive: a mixture of antioxidant 1076 and antioxidant 168 in a mass ratio of 1:2;

[0081] (2) PBT, antimony trioxide, a crystallization accelerator and an auxiliary agent are mixed in a high-speed rotating mixer, and then granulated by a twin-screw extruder to obtain a high-gloss rapid molding PBT composite material; wherein the speed of the twin-screw extruder is 400-450 rpm, and the extrusion temperature is 210-230°C.

[0082] The high-gloss rapid prototyping PBT composite material finally prepared is composed of 100 parts of PBT, 2 parts of antimony trioxide, 0.2 parts of crystallization accelerator and 0.5 parts of auxiliary agent by weight; the 60° glossiness of the high-gloss rapid prototyping PBT composite material is 99, and the crystallization temperature is 204.8°C; after the high-gloss rapid prototyping PBT composite material is placed under environmental conditions of temperature of 85°C and relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 97.2%.

Claims

1. A high gloss rapid prototyping PBT composite material, characterized in that: By weight, it is composed of 100 parts of PBT, 0.5-5 parts of nucleating agent, 0.2-1 parts of crystallization accelerator and 0.3-1 parts of auxiliary agent; The nucleating agent is antimony trioxide; The crystallization accelerator is one or more of pentaerythritol stearate, calcium stearate, and zinc stearate.

2. The high gloss rapid prototyping PBT composite material according to claim 1, characterized in that: The purity of antimony trioxide is 99.9% or more.

3. The high gloss rapid prototyping PBT composite material according to claim 1, characterized in that: The relative viscosity of PBT is 0.775-0.

87.

4. The high gloss rapid prototyping PBT composite material according to claim 1, characterized in that: The auxiliary agent is an antioxidant.

5. A high gloss rapid prototyping PBT composite material according to any one of claims 1 to 4, characterized in that: The 60° glossiness of the high-gloss rapid prototyping PBT composite material is 98.8-100.5, and the crystallization temperature is 204.2-207.3°C; after the high-gloss rapid prototyping PBT composite material is placed under the environmental conditions of temperature of 85°C and relative humidity of 85% for 240 hours, the 60° glossiness retention rate is 96.1-97.6%.

6. A method for preparing a high-gloss rapid prototyping PBT composite material as claimed in any one of claims 1 to 4, characterized in that: After mixing the components in a high-speed rotating mixer according to the proportion, the components are granulated by a twin-screw extruder to obtain a high-gloss rapid molding PBT composite material.

7. The method according to claim 6, characterized in that The speed of the twin-screw extruder is 400-450 rpm, and the extrusion temperature is 210-230°C.

Citation Information

Patent Citations

  • High heat resistance, high gloss, low volatility and rapid prototyping polybutylene terephthalate and preparation method thereof

    CN102558791A

  • Polybutylene terephthalate (PBT) composition and preparation method thereof

    CN103304965A

  • High temperature-resistant halogen-free flame retardant PBT (polybutylece terephthalate) material and preparation method thereof

    CN103756269A